Simulations of silicon nanowire sensor and an integrated smart bio-nano sensor - Chakravarthy, K. K. J.; P.S., Brahmanandam; Potukuchi, D. M.; Anil Kumar, G.; Subba Rao, N. S. (International Journal of Dental Materials, 2022)
Background: Simulation-based nano biosensors have been introduced in recent times that will provide a model for the researchers to verify various critical functions of them, which could effectively save time, money, and effort.Materials and Methods: In this study, we have performed simulations of a silicon nanowire (Si-NW) biosensor, and its various parameters were evaluated. This silicon sensor was designed using the BiosensorLab tool, a simulator from the nanohub website. This paper also presented an Integrated Smart Bio-nano Sensor. The motivation behind this smart sensor was that an incident happened in one of the southern states of India, in the year 2020; the leakage of styrene gas (C8H8) from the Polymers industry caused 12 deaths and several people hospitalized. Most people died after they inhaled styrene gas because they thought the pungent smell (of styrene gas) was also part of their kitchen’s emissions. This incident prompted us to propose an Integrated Smart Bio-nano Sensor.Results: The proposed sensor was capable of classifying the origin of sources of emissions dynamically (smart), even under lower concentrations of gas levels (25 ppm) and could alert the habitants in case of untoward danger.Conclusions: After verifying settling time vs. analyte concentration, the density of captured target molecules concentration with time vs. time, and the signal-to-noise ratio (SNR) of the biosensor in the presence of parasitic molecules vs. receptor density, it was concluded that these three parameters have helped in identifying the characteristics of the proposed bio-nano sensor.